Quantitative assessment of IgG and IgA subclass producing cells in rectal mucosa during shigellosis. - Islam, D (1997)
AIMS: To assess quantitatively both the morphological changes in the rectal mucosa and the changes in the relative frequency of IgA and IgG subclass producing cells found in the rectal mucosa during the acute phase of shigellosis and at convalescence. METHODS: Rectal biopsies from 25 Shigella dysenteriae 1 infected patients, 10 Shigella flexneri infected patients, and 40 uninfected controls were studied. Morphological changes in the mucosa were graded. The frequency of IgA and IgG subclass producing cells was assessed. In addition, immunostaining for secretory component in epithelial cells was analysed. RESULTS: Using morphological grading, 20% of the 35 patients studied had advanced inflammation (grade 3) in the acute phase of the disease. At convalescence, grade 1 inflammation was seen in 37% of the patients and in 10% of the controls. In the acute phase, as well as at convalescence, the number of IgA1, IgA2, and IgG2 positive cells was significantly higher than in the controls. The results were related to the histopathological degree of inflammation. CONCLUSIONS: In shigellosis, there is evidence for a prolonged humoral response residing in the mucosa long after the clinical symptoms have resolved, suggesting that shigellosis induces persisting mucosal humoral immune and inflammatory responses, remaining at least until 30 days after the infection.